Strategi Konten Dalam Peningkatan Engagement Rate Pada Instagram @beemahoney.id - Satria, Farhan Hierro; Abdullah, Nisa Nurmauliddiana (Jurnal Pustaka Komunikasi, 2025)
PT Beema Boga Arta, one of the companies that sells honey products, uses social media as a way to share information with its customers, under the username @beemahoney.id. PT Beema Boga Arta maximizes digital media as one of its product marketing tools, so that consumers can get to know the products produced by the company better. The purpose of designing this work is to explain how @beemahoney.id Instagram social media activities in planning content to increase engagement carried out by PT Beema Boga Arta which focuses on increasing engagement of Beema Honey at PT Beema Boga Arta within a period of 4 months from September-December 2023. The results obtained are that the Instagram social media @beemahoney.id uses a communication model, namely The Circular model of SoMe to design a content strategy on the Instagram account @beemahoney.id in increasing engagement. This research reveals that the content strategy designed by PT Beema Boga Arta through the Instagram account @beemahoney.id in the period of September-December 2023 has proven successful in increasing engagement.